2016
DOI: 10.1007/s10816-016-9292-0
|View full text |Cite
|
Sign up to set email alerts
|

Personal, Political, Pedagogic: Challenging the Binary Bind in Archaeological Teaching, Learning and Fieldwork

Abstract: In this paper, we consider how we can undercut the various binaries of gender and sexuality in archaeological practice and particularly in our teaching. We argue that taking an assemblage theory approach enables us to look at the multiplicity of identities of those practicing archaeology as different and intersecting assemblages that bring one another into being through their connections at different scales. In particular, we examine how this approach can be applied to archaeological pedagogy and how this in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
(34 reference statements)
0
7
0
4
Order By: Relevance
“…Quando restringimos a pesquisa especificamente à SAB regional Norte 3 , verificamos 91 mulheres e 59 homens, confirmando o padrão nacional de que há mais arqueólogas mulheres nos quadros da sociedade 4 . Similarmente, pesquisas amplas sobre o perfil demográfico da arqueologia no exterior têm demonstrado que o número de pesquisadoras mulheres é igual ou superior ao de homens (COBB & CROUCHER, 2016).…”
Section: Desvelando Iniquidadesunclassified
See 1 more Smart Citation
“…Quando restringimos a pesquisa especificamente à SAB regional Norte 3 , verificamos 91 mulheres e 59 homens, confirmando o padrão nacional de que há mais arqueólogas mulheres nos quadros da sociedade 4 . Similarmente, pesquisas amplas sobre o perfil demográfico da arqueologia no exterior têm demonstrado que o número de pesquisadoras mulheres é igual ou superior ao de homens (COBB & CROUCHER, 2016).…”
Section: Desvelando Iniquidadesunclassified
“…Diversos estudos revelaram, então, que as desigualdades e os preconceitos estruturais em nossa sociedade se reproduzem também dentro da arqueologia. Identidades raciais e étnicas, de gênero, classe, etc., passaram a compor o corpo de interpretações na teoria e na prática arqueológica, além de serem fundamentais para se discutir as estruturas de poder e a visibilidade de mulheres e de outros grupos minoritários dentro da academia e de postos de trabalho (CONKEY, 2003;NELSON, 2006;BATTLE-BAPTISTE, 2011;COBB & CROUCHER, 2016).…”
Section: Introductionunclassified
“…Problematizing the androcentric narratives of man the toolmaker (Bird 1993;Gero 1991;Owen 2005: 37-39;Sassaman 1998), man the hunter (Doucette 2001;Brumbach2006a, b, 2009), and man the farmer (Robin 2002(Robin , 2006Watson and Kennedy 1991), various studies of the division of labor have demonstrated that task division does not inevitably align with sex or gender, potentially exhibiting complementary, non-dichotomous, fluid, or intersectional arrangements (Brumfiel and Robin 2008;Cobb 2005;Crass 2001: 109;Geller2008: 122-124, 2009aGero and Scattolin 2002;Hendon 2002;Hollimon 2000;Brumbach 2006a, b, 2009;Joyce 1992;Levy 2006;Preston-Werner 2008;Rotman 2006;Stockett 2005). Rather than hierarchizing contexts of action and domains of inquiry according to value-laden assumptions about gender, researchers are placing greater emphasis on how such spheres intersect in multidimensional and multiscalar ways (Cobb and Croucher 2016;Ferrer 2016;Spencer-Wood 2013).…”
Section: Destabilizing the Binary Binds: Approaches To Differencementioning
confidence: 99%
“…What is at issue, then, is not only the constitution of sex and gender, nor the number of sex, gender, or sexuality categories. Also at stake is the circumscription of the ontologies of personhood and our means to recognize what kinds of bodies and identities come into existence, in the past and the present (Cobb and Croucher 2016;Matić 2016;Moral 2016).…”
Section: Normative:non-normative Tensions In Practice-the Containmentmentioning
confidence: 99%
See 1 more Smart Citation